2005
DOI: 10.1158/1078-0432.ccr-05-0466
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Cytochrome P450 Expression in Ovarian Cancer: Identification of Prognostic Markers

Abstract: Purpose: The cytochromes P450 are a multigene family of enzymes with a central role in the oxidative metabolism of a wide range of xenobiotics, including anticancer drugs and biologically active endogenous compounds. The purpose of this study was to define the cytochrome P450 profile of ovarian cancer and identify novel therapeutic targets and establish the prognostic significance of expression of individual cytochrome P450s in this type of cancer. Experimental Design: Immunohistochemistry for a panel of 23 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(193 citation statements)
references
References 31 publications
10
124
0
4
Order By: Relevance
“…Although a variety of endogenous hormones or signaling factors have been suspected to favor metastasis (Aguirre-Ghiso, 2007), little is known in this field on the effects of pollutants. Three independent studies examined cytochrome P450 profile expression in different metastatic tumors and found a significant upregulation of some AhR-target members, including CYP1B1, CYP2S1 and aromatase CYP19 (Downie et al, 2005;Kumarakulasingham et al, 2005;Haas et al, 2006), which is in line with our hypothesis. However, the mechanisms of these upregulations remain elusive particularly because other cytochrome P450 genes are also increased.…”
Section: Discussionsupporting
confidence: 86%
“…Although a variety of endogenous hormones or signaling factors have been suspected to favor metastasis (Aguirre-Ghiso, 2007), little is known in this field on the effects of pollutants. Three independent studies examined cytochrome P450 profile expression in different metastatic tumors and found a significant upregulation of some AhR-target members, including CYP1B1, CYP2S1 and aromatase CYP19 (Downie et al, 2005;Kumarakulasingham et al, 2005;Haas et al, 2006), which is in line with our hypothesis. However, the mechanisms of these upregulations remain elusive particularly because other cytochrome P450 genes are also increased.…”
Section: Discussionsupporting
confidence: 86%
“…A member of the cytochrome P450 family, CYP26A1, has recently been identified as a major RA-catabolizing enzyme, which converts RA to biologically inactive hydroxylated retinoid derivatives (Niederreither et al, 2002). CYP26A1 has been shown to be upregulated in human familial adenomatous polyposis adenomas, sporadic colon cancers and primary ovarian cancer (Downie et al, 2005;Shelton et al, 2006). Furthermore, the pattern of retinoid gene expression, including CYP26A1, has been shown to correlate with retinoid sensitivity in a panel of breast and lung cancer cell lines (Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation is plausible, because it has been shown that CYP3A43 is expressed in tissues related to steroid hormone synthesis and metabolism, and moreover in hormone related cancers, including carcinoma of the breast. [17][18][19] Thus, our finding of an association between the CYP3A43_74_delA polymorphism and poorly differentiated breast tumors adds a new candidate to the list of modulators of hormone-driven tumors. This should draw attention to CYP3A43 as a potential candidate marker for breast cancer prognosis.…”
Section: Discussionmentioning
confidence: 71%
“…17,19 As of yet, there are few studies investigating the role of CYP3A43 in health and disease. One study reported an associations of the CYP3A43*3 polymorphism with prostate cancer risk, 20 and another study showed an association of this polymorphism with grade and size of benign hyperplasia.…”
mentioning
confidence: 99%